Arabidopsis myosin XI sub-domains homologous to the yeast myo2p organelle inheritance sub-domain target subcellular structures in plant cells - Sattarzadeh, Amirali; Hanson, Maureen; Schmelzer, Elmon (Frontiers in Plant Science, 2013)
Myosin XI motor proteins transport plant organelles on the actin cytoskeleton. The Arabidopsis gene family that encodes myosin XI has 13 members, 12 of which have sub-domains within the tail region that are homologous to well-characterized cargo-binding domains in the yeast myosin V myo2p. Little is presently known about the cargo-binding domains of plant myosin XIs. Prior experiments in which most or all of the tail regions of myosin XIs have been fused to yellow fluorescent protein (YFP) and transiently expressed have often not resulted in fluorescent labeling of plant organelles. We identified 42 amino-acid regions within 12 Arabidopsis myosin XIs that are homologous to the yeast myo2p tail region known to be essential for vacuole and mitochondrial inheritance. A YFP fusion of the yeast region expressed in plants did not label tonoplasts or mitochondria. We investigated whether the homologous Arabidopsis regions, termed by us the “PAL” sub-domain, could associate with subcellular structures following transient expression of fusions with YFP in Nicotiana benthamiana. Seven YFP::PAL sub-domain fusions decorated Golgi and six were localized to mitochondria. In general, the myosin XI PAL sub-domains labeled organelles whose motility had previously been observed to be affected by mutagenesis or dominant negative assays with the respective myosins. Simultaneous transient expression of the PAL sub-domains of myosin XI-H, XI-I, and XI-K resulted in inhibition of movement of mitochondria and Golgi.